Strategi Pengembangan Usahatani Sayuran Organik Pada Kelompok Tani Syalom Di Kelurahan Rurukan Kota Tomohon - Damanik, Agnesia Septani; Pangemanan, Paulus Adrian; Lolowang, Tommy Fredy (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
The aim of this research is to develop a strategy for developing organic vegetable farming in the Syalom Farmer Group in Rurukan Village, Tomohon City. This research was carried out from April to June 2024 in Rurukan Village, Tomohon City. The sampling method in this research is purposive sampling. The data collection method used in this research is a survey method by collecting various information from several parties and conducting FGD (Focus Group Discussion). Secondary data was obtained from literature and books related to research. The data analysis used in this research is SWOT Analysis. Based on the results of research, the strategy for developing organic vegetable farming in the Syalom Farmers Group is in quadrant I, the strategy used in current conditions is to support aggressive growth policies, namely the SO strategy: 1. Improving product quality and collaborating with the government in expanding local markets as well as internationally. 2. Utilize suitable land by implementing and managing good planting patterns to produce varied products and get the right target consumers. 3. Participate in ongoing training and counseling for farmers to increase insight, skills in techniques, production and market opportunities for organic products.